2018
DOI: 10.1103/physrevapplied.10.054001
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of a Spiking Mott Artificial Neuron

Abstract: We consider the phenomenon of electric Mott transition (EMT), which is an electric induced insulator to metal transition. Experimentally, it is observed that depending on the magnitude of the electric excitation the final state may show a short lived or a long lived resistance change. We extend a previous model for the EMT to include the effect of local structural distortions through an elastic energy term. We find that by strong electric pulsing the induced metastable phase may become further stabilized by th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
(53 reference statements)
0
22
0
Order By: Relevance
“…The key physical phenomenon in those systems is an unusual thermally driven first-order insulator-metal transition, which may also be induced by a strong electric field 1416 . An important and attractive feature is that while the Mott materials are challenging to control and fabricate, they may eventually enable the replacement of the whole SCR + RC block of the “soma” with a single two-terminal Mott insulator device 17,18 . This would provide further simplicity and power efficiency for the implementation of the ultimate ultra-compact neuron 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The key physical phenomenon in those systems is an unusual thermally driven first-order insulator-metal transition, which may also be induced by a strong electric field 1416 . An important and attractive feature is that while the Mott materials are challenging to control and fabricate, they may eventually enable the replacement of the whole SCR + RC block of the “soma” with a single two-terminal Mott insulator device 17,18 . This would provide further simplicity and power efficiency for the implementation of the ultimate ultra-compact neuron 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The device returns to its original insulating state when the field is removed with a characteristic relaxation time (replicating the refractive period of neurons). That required additional short memory may come from the relaxation time of some volatile resistive switching phenomena [738] , [739] . Pickett et al [740] demonstrated that the Na gain, and the refractory period (Fig 11(a)).…”
Section: Neuristorsmentioning
confidence: 99%
“…S9 in ( 31 )]. Each node in the network can be either insulating or metallic, depending on the local temperature through a Landau-type free energy functional that mimics a first-order phase transition ( 11 , 35 ), similar to the IMT present in VO 2 and V 2 O 3 . This functional depends only on the temperature, without any direct contribution from the electric field.…”
mentioning
confidence: 99%